Long-Term Effects of Early Life Seizures on Endogenous Local Network Activity of the Mouse Neocortex - Rigas, Pavlos; Sigalas, Charalambos; Nikita, Maria; Kaplanian, Ani; Armaos, Konstantinos; Leontiadis, Leonidas Jordan; Zlatanos, Christos; Kapogiannatou, Aspasia; Peta, Charoula; Katri, Anna; Skaliora, Irini (Frontiers in Synaptic Neuroscience, 2018)
Understanding the long term impact of early life seizures (ELS) is of vital importance both for researchers and clinicians. Most experimental studies of how seizures affect the developing brain have drawn their conclusions based on changes detected at the cellular or behavioural level, rather than on intermediate levels of analysis, such as the physiology of neuronal networks. Neurons work as part of networks and network dynamics integrate the function of molecules, cells and synapses in the emergent properties of brain circuits that reflect the balance of excitation and inhibition in the brain. Therefore, studying network dynamics could help bridge the cell-to-behavior gap in our understanding of the neurobiological effects of seizures. To this end we investigated the long-term effects of ELS on local network dynamics in mouse neocortex. By using the pentylenetetrazole (PTZ)-induced animal model of generalized seizures, single or multiple seizures were induced at two different developmental stages (P9-15 or P19-23) in order to examine how seizure severity and brain maturational status interact to affect the brain’s vulnerability to ELS. Cortical physiology was assessed by comparing spontaneous network activity (in the form of recurring Up states) in brain slices of adult (>5mo) mice. In these experiments we examined two distinct cortical regions, the primary motor (M1) and somatosensory (S1) cortex in order to investigate regional differences in vulnerability to ELS. While single intermittent ELS at P19-23 had no effect on Up state activity, respective multiple seizures induced during the same period significantly changed the spectral content of spontaneous Up states by increasing their theta power. This effect was only present in S1 cortex. On the contrary, recurrent seizures at an earlier developmental stage (P9-15) had no effect. However, a prolonged single ELS during this period (P12) affected both cortices, enhancing spontaneousUp states in M1, but decreasing those in S1 cortex in terms of an overall index of Up state dynamics that integrates their occurrence and size. These results reveal that even moderate experiences of ELS can have long lasting age- and region-specific effects in local cortical network dynamics.